A problemática dos impactos ambientais das atividades minero-metalúrgicas no complexo industrial de Barcarena - Pará no período de 2003 a 2018 - JESUS, Nívia Cristina Carvalho de (2024)
The municipality of Barcarena is located in the northeast portion of the state of Pará and is limited to the north by the Bay of Guajará and the municipality of Belém, to the south by the municipalities of Mojú and Abaetetuba, to the east by the municipality of Acará and, to the west, by the do Marajó, in the southwest part, is located as the main active mining companies: Imerys and Hydro. This work aimed to discuss and historical chronology of environmental impacts. The type of research of this work is a bibliographic and documentary research. First, data and sources were collected, articles, periodicals, master's dissertations and doctoral theses were searched, as well as official documents from public agencies, especially the Instituto Evandro Chagas and the Policia Civil- Divisão Especializada em Meio ambiente e Proteção Animal (DEMAPA). After that, a reference bank was set up; and then there was a reading, analysis and discussion of the data; later the composition of the written text. The making of the maps was carried out through ArcCatalog and ArcMap and Corel Draw 2020. Thus, over 16 years of data collection, 13 environmental accidents were found. The media punctuated in the middle were described in this work in which the risks of the municipality were identified as being a drainage environment, through an alteration of the geochemical background of the rivers. It is also stated that the health of the population is vulnerable due to environmental impacts. The problem of environmental and environmental impacts caused by miningmetallurgical activities in the industrial complex of Barcarena- Pará 2003 to 2018 related to the repetitive cycle of risk and vulnerability to the environment.